The unexpected in unlikely spaces: an experience along the Rock Island corridor - Demos, Laura (Kansas State University, 2012)
Metropolitan Kansas City is a growing area, and the communities are considering new transportation options including a fixed guideway system. The addition of a fixed guideway system is often seen as controversial to people of the communities it affects, and many will not be in favor of it. Rail lines are great option for transportation because they are designed for the efficiency of getting people from place to place. However, they typically do not offer much of a visual experience to commuters. Making the transportation corridor more than just a transportation corridor through interactive, art installations will open people up to the idea of a fixed guideway system, provide trail users with destinations, and provide commuters with something interesting to look at creating a vibrant, visual experience. The RIC will become a place of destinations, recreation, vibrancy, sustainable features, and visual stimulants through the connection of the rail line, MetroGreen trails, installations, and the RIC communities. Locating literature related to the commuter rail, visual design, experience, aesthetics, and sustainability helped to determine how these elements fit into this project. Conducting precedent studies helped set guidelines for the design of installations. A process of using certain specifications in ArcGIS determined general suitability for installations resulting in twenty-eight identified sites. The development of a basic design framework through a set of matrices involving installation attributes and site conditions helped to determine site suitability for specific types of installations, which allowed me to develop a design specific to the site conditions taking the number of suitable sites down to twenty-one. Each site has a set of parameters specific to each installation. Some sites are fully designed and developed, while others are to be commissioned out to artists for design and development. This set of proposals presents a vision of the RIC as a place of destinations, recreation, vibrancy, sustainable features, and visual stimulants through the connection of the rail line, MetroGreen trails, installations, and the RIC communities. The transformation of the corridor through art installations enhances people’s experience of the corridor, promotes both the rail line and the MetroGreen trails, connects people to the corridor, and encourages sustainability.
Keywords: Rail line; Art installation; Rock Island Rail Corridor; Commuter rail; Aesthetics (0650); Landscape Architecture (0390)